The voice and the silence: hegemonía in Cleon’s representation in Thucydides’ Historiae - Franco San Román, Mariana (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2021)
Given the ubiquity of war in the Ancient Hellenic reality in general and, in particular, in the training of political leaders, the Thucydidean Cleon stands out as unusual. This article aims to identify and analyze the resources with which the historian represents the politician’s êthos in terms of his military participation. The hypothesis is that his characterization as “the most persuasive” (Thucydides 3.36.6, 4.21.3) entails an ironic attitude towards him. In a sense, his oratorical ability seems restricted to the pólis: he does not look like he has any words to offer to his soldiers on the battlefield when he faces the Spartans at Sphacteria and, much less, at the foretold defeat in Amphipolis. On this matter, Cleon’s description is eminently political and his military participation is diminished by the historian, in contrast to those of Demosthenes and Brasidas.